2019
DOI: 10.1101/655902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling pupil responses to rapid sequential events

Abstract: Pupil size is an easily accessible, noninvasive online indicator of various perceptual and cognitive processes. Pupil measurements have the potential to reveal continuous processing dynamics throughout an experimental trial, including anticipatory responses. However, the relatively sluggish (∼2 s) response dynamics of pupil dilation make it challenging to connect changes in pupil size to events occurring close together in time. Researchers have used models to link changes in pupil size to specific trial events… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…This also showed a good fit with the data (  = 0.848, range: 0.154 -0.990), as illustrated by Figures 4 and 5. Inspection of the convolution kernels derived from our modelling suggested that these provided plausible pupil dilation responses both when compared with existing literature (Denison et al, 2019;Hong et al, 2014;Knapen et al, 2016;Korn & Bach, 2016;Murphy et al, 2011), and when compared with the waveform generated when regressing estimated beliefs about surprise onto epoched data ( Figure 5). This suggests that our GLM-AR modelling approach was appropriate for analysing these data, and supports its use in future studies.…”
Section: 3glm-ar Modellingmentioning
confidence: 71%
See 3 more Smart Citations
“…This also showed a good fit with the data (  = 0.848, range: 0.154 -0.990), as illustrated by Figures 4 and 5. Inspection of the convolution kernels derived from our modelling suggested that these provided plausible pupil dilation responses both when compared with existing literature (Denison et al, 2019;Hong et al, 2014;Knapen et al, 2016;Korn & Bach, 2016;Murphy et al, 2011), and when compared with the waveform generated when regressing estimated beliefs about surprise onto epoched data ( Figure 5). This suggests that our GLM-AR modelling approach was appropriate for analysing these data, and supports its use in future studies.…”
Section: 3glm-ar Modellingmentioning
confidence: 71%
“…The design matrix X is generated by convolving a   TK  input matrix U with a gamma kernel to model the slow time course of pupil responses (Denison et al, 2019;Hoeks & Levelt, 1993;Korn & Bach, 2016). The kernel is parameterised using three parameters: shape ( h ) and scale ( l ) parameters governing the properties of the Gamma distribution, and a delay parameter ( d ) introducing a temporal delay.…”
Section: 5time-series Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The raw pupil data were converted to a data matrix using a MATLAB script, excluding data from practice and breaks between blocks. Blinks were interpolated using a cubic spline interpolation (Mathôt et al, 2013), using a dedicated Matlab function available as part of the Pupil Response Estimation Toolbox (PRET) (Denison, Parker, & Carrasco, 2019). Data were smoothed using a 20-ms moving time window, which corresponded to two refresh cycles of the LCD monitor.…”
Section: Discussionmentioning
confidence: 99%